Studi Penerapan Pembelajaran Elektronik Sebagai Strategi Pembelajaran Dosen Dan Mahasiswa di Fakultas Ilmu Komputer Universitas Al Asyariah Mandar - Rosmawati Tamin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2013)
This study refers to the application of electronic learning (e-learning) as one of the many instructional strategies in the Faculty of Computer Science of Al Asy 'Ariah Mandar University. This study aims to determine the extent to which electronic learning has been applied to optimize and to determine an increase in the quality of learning for lecturers and students through the implementation of electronic learning. The method used by descriptive study with a qualitative approach. In this study using the technique of collecting data through observation and questionnaires to the research object Force Students 2010, 2011 and 2012 as well as Lecturer at the Faculty of Computer Science of Al Asy 'Ariah Mandar University. The Result of this study indicate that the application of electronic learning need to be optimized to improve the quality of learning for both lecturers and students at the Faculty of Computer Science of Al Asyariah Mandar University.